1980
DOI: 10.3354/meps003105
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Choice of Substratum by Epifaunal Amphipods Associated with Seagrasses

Abstract: Laboratory experiments showed that the three epifaunal amphipods Cymadusa cornpta, Grandidierella bonnieroides, and Melita elongata, normally associated with seagrasses, are capable of detecting small differences in the density of seagrass and actively select areas of high blade density. When different seagrass species -Thalassia testudinurn, Syringodiurn filiforme, and Halodule wrightii -were offered with equal blade biomass, H, wrightii was selected due to its high ratio surface area: biomass. When offered e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 15 publications
1
55
1
Order By: Relevance
“…Historically, the hypothesis of differential mortality due to predation has been first proposed as the cause of the correlation between macrofauna abundance and habitat complexity (Heck & Orth, 1980;Stoner, 1980). Density-dependent mortality has been reported as the most important post-settlement factor affecting recruitment in decapods (Olmi et al, 1990;Wahle & Steneck, 1991;Eggleston & Armstrong, 1995;Palmer et al, 1996;Moksnes et al, 1997;Moksnes, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the hypothesis of differential mortality due to predation has been first proposed as the cause of the correlation between macrofauna abundance and habitat complexity (Heck & Orth, 1980;Stoner, 1980). Density-dependent mortality has been reported as the most important post-settlement factor affecting recruitment in decapods (Olmi et al, 1990;Wahle & Steneck, 1991;Eggleston & Armstrong, 1995;Palmer et al, 1996;Moksnes et al, 1997;Moksnes, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Here I examine pipefishamphipod interactions (2 fish sizes and 3 amphipod sizes) at 2 levels of habitat (artificial seagrass) complexity. Various investigators have used different measures of complexity in vegetated habitats: biomass (Orth 1977, Stoner 1980, shooWblade density (Homziak et al 1982), surface area (Stoner & Lewis 1985), and surfaceto-volume ratio (Coull & Wells 1983). I have observed gammarid amphipods to preferentially occupy the spaces between the basal portions of artificial seagrass blades, apparently reducing their conspicuousness and vulnerability to pipefish.…”
Section: Introductionmentioning
confidence: 99%
“…Nocturnal locomotory activity is well-known in seagrass-associated peracarids (Robertson & Howard 1978, Stoner 1980 and any differential dispersal characteristics could greatly influence the pattern of recruitment on Penicillus capitatus. Second, Nagle (1968) suggested that competitive interactions among peracarid species result in displacement of certain species from macroalgae.…”
Section: Discussionmentioning
confidence: 99%
“…Penicillus capitatus has 634 cm2 g-' ash-free dry wt (Lewis unpubl. ), (or 199 cm2 g-' dry wt) and Halodule wrightii has 715 cm2 g p l dry wt (Stoner 1980). Despite considerable variation in the abundance of fauna in samples of P. capitatus and H. Penicillus capitatus differed distinctively from Halodule wrightii in species composition and relative abundances (Table 4).…”
Section: Collectionsmentioning
confidence: 96%